Estradiol via estrogen receptor beta influences ROS levels through the transcriptional regulation of SIRT3 in human seminoma TCam-2 cells - Salvatore Panza; Marta Santoro; Francesca De Amicis; Catia Morelli; Valentina Passarelli; Patrizia D’Aquila; Francesca Giordano; Erika Cione; Giuseppe Passarino; Dina Bellizzi; Saveria Aquila (Tumor Biology, 2017)
Human testis, gonocytes, and adult germ cells mainly express estrogen receptor beta, and estrogen receptor beta loss is associated with advanced tumor stage; however, the molecular mechanisms of estrogen receptor beta–protective effects are still to be defined. Herein, we provide evidence that in human seminoma TCam-2 cells, E2 through estrogen receptor beta upregulates the mitochondrial deacetylase sirtuin-3 at protein and messenger RNA levels. Specifically, E2 increases sirtuin-3 expression through a transcriptional mechanism due to the occupancy of sirtuin-3 promoter by estrogen receptor beta, together with the transcription factor Sp1 as evidenced by Chip reChIp assay. This complex binds to a GC cluster located between −128 bp/+1 bp and is fundamental for E2 effects, as demonstrated by Sp1 small interfering RNA studies. Beside, after 24 h, E2 stimulus significantly increased activities of superoxide dismutase and catalase to scavenge reactive oxygen species produced by 30 min of E2 stimulus. In summary, this article indicates a novel functional interplay between estrogen receptor beta and sirtuin-3 counteracting reactive oxygen species production in TCam-2 cells. Our findings thus show that an important tumor-suppressive pathway through estrogen receptor beta is target of E2, actually proposing a distinctive protecting action against seminoma. Future studies may lead to additional strategies for the current therapy of seminoma.